2017
DOI: 10.4209/aaqr.2016.07.0310
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Exposure during Preventive Maintenance of an Ion Implanter in a Semiconductor Manufacturing Factory

Abstract: Workers in the semiconductor fabrication process may be exposed to higher levels of hazardous materials, such as arsenic, during preventive maintenance (PM) tasks than during the regular operation of the fabrication process. This study investigates the exposure to arsenic and other metals during PM tasks in the ion implantation process. Airborne arsenic samples and bulk samples were obtained during various ion implanter PM tasks in a semiconductor fabrication factory. The arithmetic mean (AM) and standard devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In this study, we also confirmed arsenic exposure possibility of workers during preventive maintenance of ion implanters. The more detailed information can be found from another article published [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we also confirmed arsenic exposure possibility of workers during preventive maintenance of ion implanters. The more detailed information can be found from another article published [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticles less than 100 nm in diameter are emerging, and the occupational health issues associated with these are unknown. The investigation of exposure to nanoparticles is actively performed in many occupational settings, such as engineered nanoparticle manufacturing workplaces, welding, 3D printing, and even the semiconductor industry [24][25][26]. Figure 3g shows that the particles shown in Figure 3f consisted of carbon and oxygen, as analyzed using EDS.…”
Section: Status Of Indoor Air Quality In the Fire Stationmentioning
confidence: 99%
“…The American Conference of Governmental Industrial Hygienists (ACGIH) has set threshold limit values (TLVs). In nearly all cases, the regulations are mass-based and do not differentiate between sizes of airborne particles or consider the unique toxicity considerations for nanoparticles due to their small size, high surface area, and unique physicochemical properties [20,21]. To date, only ultrafine titanium dioxide and carbon nanotubes have a size-resolved exposure limit [22,23].…”
Section: Introductionmentioning
confidence: 99%